The contribution of oncovascular surgery in a young patient with idiopathic retroperitoneal fibrosis. Issue 1 (17th January 2022) - Kotsis, Thomas; Christoforou, Panagitsa; Polydorou, Andreas
Abstract: Surgical resection remains the cornerstone for the treatment of oncological disease. When a critical arterial or venous structure is involved in a tumor mass, successful relief of symptoms and long-term oncological control are achieved through careful preoperative planning by an interdisciplinary team that necessarily includes a vascular surgeon. We describe the involvement of a vascular surgeon in the oncology of a 22-year-old woman, who is diagnosed with idiopathic retroperitoneal fibrosis.